Expressing stemflow commensurate with its ecohydrological importance. (November 2018) - Carlyle-Moses, Darryl E.; Iida, Shin'ichi; Germer, Sonja; Llorens, Pilar; Michalzik, Beate; Nanko, Kazuki; Tischer, Alexander; Levia, Delphis F.
Abstract: Despite some progress, the importance of stemflow remains obscured partly due to computations emphasizing canopy interception loss. We advocate for two metrics—the stand-scale funneling ratio and the stand-scale infiltration funneling ratio—to more accurately portray stemflow inputs and increase comparability across ecosystems. These metrics yield per unit area stemflow inputs orders of magnitude greater than what would have been delivered by throughfall or precipitation alone. We recommend that future studies employ these stand-scale funnelling metrics to express stemflow commensurate with its ecohydrological importance and better conceptualize the role of stemflow in plant-soil interactions, permitting advances in critical zone science.